Curcumin as chemosensitizer - Pornngarm Limtrakul (2018)
This overview presents curcumin as a significant chemosensitizer in cancer chemotherapy. Although the review focuses on curcumin and its analogues on multidrug resistance (MDR) reversal, the relevance of curcumin as a nuclear factor (NF)-κB blocker and sensitizer of many chemoresistant cancer cell lines to chemotherapeutic agents will also be discussed. One of the major mechanisms of MDR is the enhanced ability of tumor cells to actively efflux drugs, leading to a decrease in cellular drug accumulation below toxic levels. © 2007 Springer.